Supportive care for systemic amyloidosis: International Society of Amyloidosis (ISA) expert panel guidelines - Muchtar, Eli; Grogan, Martha; Siepen, Fabian aus dem; Waddington-Cruz, Marcia; Misumi, Yohei; Carroll, Antonia S.; Clarke, John O.; Sanchorawala, Vaishali; Milani, Paolo; Caccialanza, Riccardo; Da Prat, Valentina; Pruthi, Rajiv; et al. (Amyloid, 2025)
Systemic amyloidosis refers to a group of protein misfolding disorders resulting in organ deposition with amyloid, leading to organ dysfunction, ultimately resulting in organ failure and death if not successfully treated. Treatment is type-specific and aimed at the underlying source of the misfolded protein. In the past decades, treatments have become increasingly available across the various amyloidosis types with improved response rates and longer survival. Supportive care measures are an integral part of care for patients with systemic amyloidosis to improve symptom burden and quality of life, reduce healthcare costs, and potentially prolong survival while type-directed therapy takes effect. In these guidelines, we provide supportive care recommendations across eight areas of interest in systemic amyloidosis: cardiology, nephrology, peripheral neuropathy, central nervous system involvement, autonomic neuropathy, gastroenterology, coagulopathy and bleeding, nutrition and hematology. These guidelines were developed on behalf of the International Society of Amyloidosis (ISA) by experts in the above fields and provide the best available evidence and expertise for supportive care in these rare disorders.